Mcl-1 Inhibition: Managing Malignancy in Multiple Myeloma - Al-Odat, Omar S.; von Suskil, Max; Chitren, Robert J.; Elbezanti, Weam O.; Srivastava, Sandeep K.; Budak-Alpddogan, Tulin; Jonnalagadda, Subash C.; Aggarwal, Bharat B.; Pandey, Manoj (Frontiers in Pharmacology, 2021)
Multiple myeloma (MM) is a plasma cells neoplasm. The overexpression of Bcl-2 family proteins, particularly myeloid cell leukemia 1 (Mcl-1), plays a critical role in the pathogenesis of MM. The overexpression of Mcl-1 is associated with drug resistance and overall poor prognosis of MM. Thus, inhibition of the Mcl-1 protein considered as a therapeutic strategy to kill the myeloma cells. Over the last decade, the development of selective Mcl-1 inhibitors has seen remarkable advancement. This review presents the critical role of Mcl-1 in the progression of MM, the most prominent BH3 mimetic and semi-BH3 mimetic that selectively inhibit Mcl-1, and could be used as single agent or combined with existing therapies.